Bioactive molecules from terrestrial and seafood resources in hypertension treatment: focus on molecular mechanisms and targeted therapies - Md. Rezaul Islam; Puja Sutro Dhar; Shopnil Akash; Sabeena Hussain Syed; Jeetendra Kumar Gupta; Kumaraswamy Gandla; Muniya Akter; Abdur Rauf; Hassan A. Hemeg; Yasir Anwar; Bassam Oudh Aljohny; Polrat Wilairatana (Natural Products and Bioprospecting, 2023)
Abstract Hypertension (HTN), a complex cardiovascular disease (CVD), significantly impacts global health, prompting a growing interest in complementary and alternative therapeutic approaches. This review article seeks to provide an up-to-date and thorough summary of modern therapeutic techniques for treating HTN, with an emphasis on the molecular mechanisms of action found in substances found in plants, herbs, and seafood. Bioactive molecules have been a significant source of novel therapeutics and are crucial in developing and testing new HTN remedies. Recent advances in science have made it possible to understand the complex molecular mechanisms underlying blood pressure (BP)-regulating effects of these natural substances better. Polyphenols, flavonoids, alkaloids, and peptides are examples of bioactive compounds that have demonstrated promise in influencing several pathways involved in regulating vascular tone, reducing oxidative stress (OS), reducing inflammation, and improving endothelial function. The article explains the vasodilatory, diuretic, and renin–angiotensin–aldosterone system (RAAS) modifying properties of vital plants such as garlic and olive leaf. Phytochemicals from plants are the primary in traditional drug development as models for novel antihypertensive drugs, providing diverse strategies to combat HTN due to their biological actions. The review also discusses the functions of calcium channel blockers originating from natural sources, angiotensin-converting enzyme (ACE) inhibitors, and nitric oxide (NO) donors. Including seafood components in this study demonstrates the increased interest in using bioactive chemicals originating from marine sources to treat HTN. Omega-3 fatty acids, peptides, and minerals obtained from seafood sources have anti-inflammatory, vasodilatory, and antioxidant properties that improve vascular health and control BP. Overall, we discussed the multiple functions of bioactive molecules and seafood components in the treatment of HTN.